A Cross-Sectional Analysis on Maternal Mental Health and Severity of Acute Malnutrition among Children Admitted in Nutritional Rehabilitation Centres of Karnali Province, Nepal - K.C, Shreejana; Lama, Nishant; Lama, Monika; Giri, Rajendra Mani; Neupane, Pratima; Pun, Bibek; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2025)
Background: The quality of nutritional care provided to children is determined by mother’s psychological involvement with children. Acute malnutrition among children plays pivotal role in causation of morbidity, mortality and intergenerational inequity. Therefore, determining determinants of maternal mental health status and its association with severity of acute malnutrition was the primary objective of the study. Methods: A cross-sectional study was conducted from Jan 2023 to April 2023 among 105 mother and child dyad admitted in Nutritional Rehabilitation Centres (NRCs) of Karnali Province. WHO Self-Reporting Questionnaire-20 was used to assess maternal mental distress and admission record was noted to identify the severity of acute malnutrition in children. Descriptive and inferential analysis was done. Ethical principles were minded throughout the study period. Results: Severe acute malnutrition rehabilitation was received by 69.5% of children admitted in NRCs where majority (80.6%) of them belonged to mothers having mental distress. Intimate Partner Violence was the prime factor associated with maternal mental distress (p=0.001) and severity of acute malnutrition (p=0.038) in children. Age of child (p=0.043) and frequency of consumption of cereals (p=0.032), pulses (p=0.001), animal products (p=0.036) and vegetables (p=0.001) were associated with severity of acute malnutrition. Conclusions: Over two third of children were severely acute malnourished and one third of mothers had mental distress. Intimate partner violence was detrimental to maternal mental distress and severity of acute malnutrition. Tailoring mental health and One Stop Crisis Management Centre services to the mothers at Nutritional Rehabilitation Centre and promoting infant and young child feeding would be a game changer in management of acute malnutrition in Nepal